A Retrospect of the Special Issue "Advances in Oral Implant Health" - Andrea Butera; Andrea Scribante (MDPI AG, 2023)
Research on modern dental implantology focuses on the development of increasingly more advanced techniques with the aim of improving the reliability of dental implants while reducing patient morbidity [...]